O erotismo e o sagrado no livro A história do olho de George Bataille - Silvane Santos SOUZA; Eliane Bispo de Almeida SOUZA (Entrepalavras: Revista de Linguística do Departamento de Letras Vernáculas da Universidade Federal do Ceará)
This article aims to discuss one of George Bataille thoughts, from the analysis of the erotic novel Story of the eye, one of his most outstanding works. The History of the eye is filled with narrative scenes where the image of the eye is seen as a transfigurável object. In this book, Bataille argues heterogeneous when discussing topics such as eroticism and sacred, addressed a vision that opposes the discourse of a bourgeois society that preaches what is homogeneous, showing from the erotic scenes confrontation to “normality” of the society of the time, with the presentation of situations to a certain surreal point, endowed with transgression. Thus, the discussion points out that the work of Bataille seeks to repudiate the issues taken for granted essentially on eroticism and sexuality, as the latter is stated as unproductive expenditure, overspending and completely sterile, because sex is not presented as source of relief or satiety but as a great distress. A milestone that distinguishes the work is the relationship between sexuality, sacred and eroticism, going beyond simple sexual adventure, for the pursuit of “orgasm” through the eye imagery. To discuss these issues, the ideas presented here are backed up in the following authors: George Bataille, Barthes, Wasghinton Drumonnd, Jürgen Habermas, Philippe Joron, Michel Leiris and Eliane Moraes.